E-074 Relationship between symptomatic presentation and aneurysmal wall enhancement in unruptured intracranial saccular aneurysms. (22nd July 2018) - Fang, Y; Brinjikji, W; Cancelliere, N; Byun, J; Radovanovic, I; Krings, T; Pereira, V
Abstract : Objective: To study the correlation between clinical symptoms and aneurysm wall enhancement (AWE) on high-resolution vessel wall imaging in a consecutive series of unruptured intracranial saccular aneurysms (IAs). Methods: We performed high-resolution vessel wall magnetic resonance imaging in a consecutive cohort of patients. Images were evaluated by two neuroradiologists for the presence of AWE. We studied the association between the symptomatic status of an aneurysm and AWE. Symptomatic aneurysms were defined as those associated with an atypical headache (sentinel) and cranial nerve palsy. Results: Sixteen patients with 20 aneurysms (9 symptomatic and 11 asymptomatic) were included. After the high-resolution magnetic resonance imaging was performed, AWE was detected in the total of 8 aneurysms. The proportion of AWE was comparable in symptomatic versus asymptomatic aneurysms (p=1.000). However, symptomatic aneurysms were more frequently located in larger arteries including internal carotid artery and basilar artery (p=0.014). Aneurysms with AWE were proved to have a larger size of aneurysm height (p=0.044), aneurysm neck (p=0.089), and maximal diameter (p=0.066). Conclusions: In unruptured intracranial saccular aneurysms, there is no correlation between clinical presentation of unruptured IAs and AWE on high-resolution vessel wall imaging. Larger aneurysms are presumably risk factor for AWE. Disclosures: Y. Fang: None. W. Brinjikji: None. N. Cancelliere: None. J. Byun: None. I. Radovanovic: None. T. Krings: None. V. Pereira: None.